Multidisciplinary Treatment of Non-Spine Bone Metastases: Results of a Modified Delphi Consensus Process. (July 2022) - Gillespie, Erin F.; Mathis, Noah J.; Vaynrub, Max; Santos Martin, Ernesto; Kotecha, Rupesh; Panoff, Joseph; Salner, Andrew L.; McIntosh, Alyson F.; Gupta, Ranju; Gulati, Amitabh; Yerramilli, Divya; Xu, Amy J.; et al.
Highlights: Evidence is emerging for new paradigms in the management of non-spine bone metastases. Consensus was feasible amongst physicians in both academic and community-based practice settings. Topics deemed of highest importance for consensus included referral for surgical stabilization and approach to peri -operative radiation, preferred radiation fractionation and appropriate use of stereotactic techniques, and clinical scenarios classified as potentially "complex" warranting multidisciplinary discussion. Abstract: Purpose: Local treatment for bone metastases is becoming increasingly complex. National guidelines traditionally focus only on radiation therapy (RT), leaving a gap in clinical decision support resources available to clinicians. The objective of this study was to reach expert consensus regarding multidisciplinary management of non-spine bone metastases, which would facilitate standardizing treatment within an academic-community partnership. Methods and Materials: A multidisciplinary panel of physicians treating metastatic disease across the Memorial Sloan Kettering (MSK) Cancer Alliance, including community-based partner sites, was convened. Clinical questions rated of high importance in the management of non-spine bone metastases were identified via survey. A literature review was conducted, and panel physicians drafted initial recommendation statements. Consensus was gathered on recommendation statements through a modified Delphi process from a full panel of 17 physicians from radiation oncology, orthopaedic surgery, medical oncology, interventional radiology, and anesthesia pain. Consensus was defined a priori as 75% of respondents indicating "agree" or "strongly agree" with the consensus statement. Strength of Recommendation Taxonomy was employed to assign evidence strength for each statement. Results: Seventeen clinical questions were identified, of which 11 (65%) were selected for the consensus process. Consensus was reached for 16 of 17 answer statements (94%), of which 12 were approved after Round 1 and additional 4 approved after Round 2 of the modified Delphi voting process. Topics included indications for referral to surgery or interventional radiology, radiation fractionation and appropriate use of stereotactic approaches, and the handling of systemic therapies during radiation. Evidence strength was most commonly C (n = 7), followed by B (n = 5) and A (n = 3). Conclusions: Consensus among a multidisciplinary panel of community and academic physicians treating non-spine bone metastases was feasible. Recommendations will assist clinicians and potentially provide measures to reduce variation across diverse practice settings. Findings highlight areas for further research such as pathologic fracture risk estimation, pre-operative radiation, and percutaneous ablation.